Heterogeneous system architecture : a new compute platform infrastructure - Hwu, Wen-mei (Morgan Kaufmann, 2016)
This book presents a next-generation hardware platform, and associated software, that allows processors of different types to work efficiently and cooperatively in shared memory from a single source program. HSA also defines a virtual ISA for parallel routines or kernels, which is vendor and ISA independent thus enabling single source programs to execute across any HSA compliant heterogeneous processer from those used in smartphones to supercomputers. Topics include: overview of the evolution of heterogeneous parallel processing, associated problems, and how they are overcome with HSA; runtime, memory model, queuing, context switching, the architected queuing language, simulators, and tool chains; three real world examples are presented, which provide an early demonstration of how HSA can deliver significantly higher performance thru C++ based applications. --